Counseling and psychotherapy with religious persons : a rational emotive behavior therapy approach - Nielsen, Stevan Lars (LEA series in personality and clinical psychology., 2001)
This may be the most practical and user-friendly guide to treating religious persons ever published. Mental health professionals from all backgrounds will benefit from the author's detailed yet manual-focused apprch to help overcome emotional distress. &